Pemanfaatan Arduino Uno Sebagai Pengendali Otomatis Ruang Perawatan Bayi Prematur - Arsanto Narendro; Tatang Wirawan Wisnuadji; Turkhamun Adi Kurniawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Currently, many automatic and practical tools have been created. Including in the world of health, for example baby incubators. Baby incubators are generally used for babies born prematurely. Baby incubators generally still use manual methods in controlling the temperature of the incubator room, for example the temperature in the incubator is above the ideal temperature, or even the temperature is below the required temperature. So the role of the operator, in this case the doctor or nurse, is still dominant. With this problem, we need a system that can control and monitor the baby incubator temperature based on web and SMS, making it easier for doctors and nurses to monitor the baby's condition. This tool will be developed to be web and SMS based. With the development of this tool, it is hoped that it can help doctors and nurses in monitoring the condition of babies in incubators.